[Дневник и литературные наброски. 20 октября 1908 г. – 3 мая 1911 г.] - Крусман, Владимир Эдуардович (Б.м., 1911)
Шифр рукописи: 700-р 1388/с.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Literature; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; литературные наброски; дневник; Крусман Володимир Едуардович (1879 - 1922); щоденник; літературні начерки